The innovator's guide to growth : putting disruptive innovation to work - Anthony, Scott D. (Boston, Mass. : Harvard Business Press, 2008)
More than a decade ago 'The Innovator's Dilemma' illustrated how disruptive innovations drive industry transformation and market creation. This volume extends Christensen's research, demonstrating further how growth-seeking incumbents must develop the capability to deflect disruptive attacks and seize disruptive opportunities.
Precursors to innovation -- pt. 1. Identify opportunities. Identifying nonconsumers ; Identifying overshot customers ; Identifying jobs to be done -- pt. 2. Formulate and shape ideas. Developing disruptive ideas ; Assessing a strategy's fit with a pattern -- pt. 3. Build the business. Mastering emergent strategies ; Assembling and managing project teams -- pt. 4. Build capabilities. Organizing to innovate ; Innovation metrics.
Includes bibliographical references (pages 281-288) and index.
Description based on print version record.
Keywords: Technological innovations -- Management; Disruptive technologies -- Management; New products; Business planning; Produktinnovation; Technische Innovation; Unternehmensplanung; Produktinnovation; Technische Innovation; Unternehmensplanung; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books